Meningkatkan Hasil Belajar PPKn Menggunakan Model PBL, STAD, dan Talking Stick Pada Siswa Kelas IV SD - Yasmin Pitiyanova; Ahmad Muhyani Rizalie (Universitas PGRI Palembang, 2021)
Abstract: The problem raised in this study is tje low learning outcomes of fourth grdae students at SDN Kelayan Timur 5 Banjarmasin on PPKn content. The cause of these problems are learning that does not trigger students’ skills in critical thingking, learning is only centered on teachers and theme books, and lack of motivation and interest in student learning. The effort made to address this issue is by using a combination of PBL, STAD, and Talking stick models. The research aims to describe the quality of teacher and student activities, as well as analyze the improvement in students’ learning outcomes. A qualitative approach with Classroom Action Research (CAR) was conducted for three meetings at SDN Kelayan Timur 5 Banjarmasin during the 2022/2023 academic year, involving 25 fourth grade students. The research was carried out on the them “The Beauty of Diversity in My Country” in the subject of Civics. The data collected included teacher activities, student activities, and students’ learning outcomes, which were analyzed using percentage scales and classical learning achievement indicators. The results showed that the combination of PBL, ATAD, and Talking Stick models in the third meeting resulted in excellent teacher activities with a score of 98, highly active atudent activities with a score of 100%, and cognitive and affectve learning outcomes reaching 100% proficiency. Based on the findings, it can be concluded that using this combination of teaching models can enhance teacher activities, student engagement, and learning outcomes in the subject of Civics, “The Beauty of Diversity in My Country.” Teachers are advised to utilize this combination of models to create learning activities that enhance student motivation, interaction, and engagement, leading to improved student learning outcomes. Keywords: Learning Outcomes, PPKn, PBL, STAD, Talking Stick. Abstrak: permasalahan yang diangkat dalam penelitian ini adalah rendahnya hasil belajar siswa kelas IV SDN Kelayan Timur 5 Banjarmasin pada muatan PPKn. Penyebab dari masalah tersebut adalah pembelajaran yang kurang memicu keterampilan siswa dalam berpikir kritis, pembelajaran hanya berpusat pada guru dan buku tema, serta kurangnya motivasi dan minat belajar siswa. Hal yang dilakukan sebagai upaya mengatai masalah yaitu dengan menggunakan kombinasi model PBL, STAD, dan Talking Stick. Tujuan dari penelitian ini untuk mendeskripsikan kualitas aktivitas guru dan aktivitas siswa, serta menganalisis peningkatan hasil belajar siswa pada muatan PPKn Tema 7 Indahnya Keragaman di Negeriku pada siswa kelas IV SDN Kelayan Timur 5 Banjarmasin. Subjek penelitian ini berjumlah 25 orang. Penelitian ini menggunakan pendekatan kualitatif dengan jenis PTK. Jenis data yang diperolah mencakup aktivitas guru, aktivitas siswa, dan hasil belajar siswa yang dianalisis menggunakan skala persentase dan indikator keberhasilan. Hasil penelitian menunjukkan bahwa kombinasi model PBL, STAD, dan Talking Stick pada pertemuan III menghasilkan aktivitas guru dengank kategori sangat baik dengan perolehan skor 98, aktivitas siswa dengan kategori sangat aktif dengan perolehan skor 100%, dan hasil belajar kognitif dan afektif mencapai ketuntasan 100%. Berdasarkan hasil penelitian, disimpulkan bahwa pembelajaran dengan menggunakan kombinasi model PBL, STAD, dan Talking Stick dapat meningkatkan aktivitas dan hasil belajar. Kata kunci: Hasil Belajar, PPKn, PBL, STAD, Talking Stick